1996
DOI: 10.1183/09031936.96.09020196
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the dose of inhaled steroid affect exhaled nitric oxide levels in asthmatic patients

Abstract: An increased concentration of nitric oxide (NO) in the exhaled air of asthmatic patients may reflect inflammation of the airways, and exhaled NO may, therefore, be useful in monitoring asthma control and the optimal use of anti-inflammatory treatment.We have studied the effect of reducing and then increasing the dose of inhaled steroid on exhaled NO, lung function and symptoms in 14 asthmatic patients treated with twice daily budesonide. Baseline measurements were made at the end of a 2 week run-in period, 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
131
2
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(150 citation statements)
references
References 25 publications
11
131
2
6
Order By: Relevance
“…It may be possible that in the relatively more severe subjects, for whom a regular anti-inflammatory treatment was necessary, the measurement of airway flow is less sensitive in evaluating the severity of the disease as compared to airway inflammation as evaluated by ENO. This is in agreement with the finding by KARITONOV and coworkers [19,20] who showed that significant changes of ENO levels induced by the introduction of treatment with budesonide [20] or mod-ulation of its dosage [19] were not accompanied by signi-ficant modifications in FEV1 levels.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It may be possible that in the relatively more severe subjects, for whom a regular anti-inflammatory treatment was necessary, the measurement of airway flow is less sensitive in evaluating the severity of the disease as compared to airway inflammation as evaluated by ENO. This is in agreement with the finding by KARITONOV and coworkers [19,20] who showed that significant changes of ENO levels induced by the introduction of treatment with budesonide [20] or mod-ulation of its dosage [19] were not accompanied by signi-ficant modifications in FEV1 levels.…”
Section: Resultssupporting
confidence: 93%
“…Some studies have evaluated the effect of treatment with inhaled steroids on the levels of ENO in asthmatic adults [19,20] and one study in children with acute asthma [21]. Furthermore, a few studies have evaluated the relationship of this parameter with the level of airway hyperresponsiveness with contrasting results [22±25].…”
mentioning
confidence: 99%
“…Furthermore, inhaled corticosteroids decrease exhaled NO (eNO) [4,5]. These results support the argument that eNO level is a marker of airway inflammation and suggest that measurement of eNO may be important in the management of asthma [6].…”
Section: Introductionsupporting
confidence: 58%
“…The forced expiratory volume in one second (FEV1) and forced mid-expiratory flow (FEF25±75) were considered in the analysis of results. The FE,NO was measured using a chemiluminescence analyser (Logan LR 2149; Logan, Rochester, UK) before performing spirometry [14,15].…”
Section: Lung Function and Nitric Oxide Measurementmentioning
confidence: 99%
“…Recent studies have shown that inhaled corticosteroids are capable of decreasing the FE,NO in asthmatic patients in a dose-dependent fashion [14,15].…”
mentioning
confidence: 99%